Promoting Environmental Awareness in the English Class Using Task-Based Teaching (2016)
ABSTRACT: This Action Research project analyzed the impact of tasks to promote environmental awareness and to foster students’ English learning. The participants were fifth graders from the educational institution Normal Superior de Envigado. Data were collected through the implementation of several instruments: my journal, students’ work, a focus group with eight students, and an interview to the CT. The development of this project brought interesting results, namely, the viability to work on tasks as a strategy to develop environmental awareness, and to improve students’ English learning, motivation, and self-confidence.